Current Perspectives on Gastrointestinal Models to Assess Probiotic-Pathogen Interactions - Anjum, Mehreen; Laitila, Arja; Ouwehand, Arthur C.; Forssten, Sofia D. (Frontiers in Microbiology, 2022)
There are different models available that mimic the human intestinal epithelium and are thus available for studying probiotic and pathogen interactions in the gastrointestinal tract. Although, in vivo models make it possible to study the overall effects of a probiotic on a living subject, they cannot always be conducted and there is a general commitment to reduce the use of animal models. Hence, in vitro methods provide a more rapid tool for studying the interaction between probiotics and pathogens; as well as being ethically superior, faster, and less expensive. The in vitro models are represented by less complex traditional models, standard 2D models compromised of culture plates as well as Transwell inserts, and newer 3D models like organoids, enteroids, as well as organ-on-a-chip. The optimal model selected depends on the research question. Properly designed in vitro and/or in vivo studies are needed to examine the mechanism(s) of action of probiotics on pathogens to obtain physiologically relevant results.